2020
DOI: 10.3389/fphys.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Respiratory Physiology in Cetaceans

Abstract: In the current study, we used breath-by-breath respirometry to evaluate respiratory physiology under voluntary control in a male beluga calf [Delphinapterus leucas, body mass range (M b): 151-175 kg], an adult female (estimated M b = 500-550 kg) and a juvenile male (M b = 279 kg) false killer whale (Pseudorca crassidens) housed in managed care. Our results suggest that the measured breathing frequency (f R) is lower, while tidal volume (V T) is significantly greater as compared with allometric predictions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…V T values presented here are about half of the mean mass‐relative V T values reported for captive Tursiops (Ridgway et al, 1969; Fahlman et al, 2016) or Orcinus (Kreite, 1995), but 60%–80% higher than that predicted by Stahl's (1967) allometric relationship for terrestrial mammals. These results generally agree with Fahlman et al (2020), who reported consistently higher V T higher in marine mammals than in terrestrial mammals. Fahlman et al (2016) found that both V T and f v increased with exercise, but did not report how simultaneous measures of additional variables, such as t E , might have reduced the observed large variability in V T .…”
Section: Discussionsupporting
confidence: 92%
“…V T values presented here are about half of the mean mass‐relative V T values reported for captive Tursiops (Ridgway et al, 1969; Fahlman et al, 2016) or Orcinus (Kreite, 1995), but 60%–80% higher than that predicted by Stahl's (1967) allometric relationship for terrestrial mammals. These results generally agree with Fahlman et al (2020), who reported consistently higher V T higher in marine mammals than in terrestrial mammals. Fahlman et al (2016) found that both V T and f v increased with exercise, but did not report how simultaneous measures of additional variables, such as t E , might have reduced the observed large variability in V T .…”
Section: Discussionsupporting
confidence: 92%
“…That is, smaller aquatic and terrestrial mammals take similar-sized breaths, whereas large aquatic mammals take larger breaths than large terrestrial mammals. Comprehensively, the aquatic breathing (Stahl, 1967), breathing frequency aquatic = 33•body mass −0.42 (Mortola & Limoges, 2006), (e) tidal volume terrestrial = 7.69•body mass 1.04 (Stahl, 1967), tidal volume aquatic = 0.0372•body mass 0.92 (Fahlman et al, 2020), (f) cardiac output = 187•body mass 0.81 (Stahl, 1967), and (g) minute ventilation = 379•body mass 0.80 (Stahl, 1967). In panels a-d, dots are observed data points and colored lines with shaded regions are population-average model predictions with 95% confidence intervals.…”
Section: Higher Bmrs In Small Aquatic Mammalsmentioning
confidence: 99%
“…R. Soc. B 376: 20200223 in small-and medium-sized cetaceans [60]. The start of a breath was determined from the flow signal and the f R was determined from the duration between successive breaths.…”
Section: (B) Data Collectionmentioning
confidence: 99%